Prospective study on outcome of post-partum intrauterine contraceptive device insertion at tertiary level rural health institute of Gujarat, India - Ninama, Shilpa N.; Shah, Tejas A.; Gandhi, Mayur R. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: This study was conducted to evaluate the acceptance, safety, efficacy, complications and expulsion rate of post-partum intrauterine contraceptive device (PPIUCD) insertion among post-partum pregnant women in a rural tertiary care center. Objective of this study was assessment of the efficacy and safety of post-partum IUCD insertion. Comparing the complications and client satisfaction in both groups (intra caesarean insertion versus vaginal route of insertion). Methods: This is a prospective study conducted at one of the rural tertiary care teaching institution. A total of 150 patients with caesarean or vaginal deliveries had PPIUCD insertions and they were followed up for a period of one year. The outcome measures analyzed were menstrual irregularities, vaginal discharge, pelvic infection and perforation and efficacy measures - failure, expulsion and removal. Data are expressed in frequency and percentage. Chi square test was used for comparison and P value <0.05 was considered significant. Results: The study shows that PPIUCD is an effective intervention in both caesarean and vaginal delivery with non-significant differences in safety and efficacy depending on the route of insertion. There was no case of perforation and no significant risk of infection in either caesareans or delivery. Spontaneous expulsion occurred in two cases inserted by vaginal route. Missing string incidence is high in the caesarean group compared to vaginal insertion. Conclusions: PPIUCD is a safe, effective and long term reversible method of contraception and should be encouraged by public awareness and community acceptance.